ARSMEDICA: AN ARTIFICIAL INTELLIGENCE–DRIVEN PLATFORM FOR SCHOLARLY DATABASE NAVIGATION AND SCIENTIFIC PUBLISHING SUPPORT (Global Conference on Medical and Health Sciences, 2026)
The rapid growth of scientific information has considerably complicated the process of identifying reliable scholarly databases, appropriate academic journals, and relevant scientific events. Researchers, particularly students and early-career scientists, often encounter difficulties when attempting to locate trustworthy publishing platforms and establish communication with editorial offices. As a result, the dissemination of scientific research may become inefficient and time-consuming.
Keywords: artificial intelligence, scholarly databases, academic publishing, research, platforms, scientific communication, digital research infrastructure, Ai-assisted academic writing, research information systems.